Factors Influencing Acceptance of Technology by Senior Citizens: A Systematic Review - Abu Seman, A.H. (Springer, 2020)
People are living much longer worldwide than they were two decades ago. Life expectancy has been increasing since the early twentieth centuries 1. As a consequence, senior citizen population in the nations also increase. However, fewer elderly lives with their children than they did in the past. This concern was raised up and resulting in the development of the high technology devices, equipment and applications that aid and improve their quality of life. Despite of the improvement that have been developed, it has been found that technology acceptance, and thus technology adoption, is relatively low among senior citizens to compare with younger adults. Therefore, a systematic literature review was performed to identify the factors influencing acceptance of technology by these populations and the research models used to measure them. Many research papers from different databases have been reviewed on basis of inclusion and exclusion criteria. The review identified ten factors influencing acceptance of technology and ten research models used in measuring the factors. The findings of this research are the work of researchers that will be beneficial for those who are interested in finding interesting area of research in this field. Â© 2020, Springer Nature Switzerland AG.